Vibrations in a fluid-loaded poroelastic hollow cylinder surrounded by a fluid in plane-strain form - Shanker, Bandari; Nath, C. Nageswara; Shah, Ahmed S.; Reddy, P.M. (Zielona Góra: Uniwersytet Zielonogórski)
Plane-strain vibrations in a fluid-loaded poroelastic hollow cylinder surrounded by a fluid are investigated employing Biot`s theory of wave propagation in poroelastic media. The poroelastic hollow cylinder is homogeneous and isotropic, while the inner and outer fluids are homogeneous, isotropic and inviscid. The frequency equation of the fluid-loaded poroelastic cylinder surrounded by a fluid is obtained along with several particular cases, namely, fluid-loaded poroelastic cylinder, fluid-loaded bore, poroelastic cylinder surrounded by a fluid and poroelastic solid cylinder submerged in a fluid.
Keywords: Biot`s theory; fluid-loaded poroelastic cylinder; frequency; submerged poroelastic cylinder; plane-strain vibrations; phase velocity